ED visits and hospital admissions of foreigners for psychiatric disorders in Rome from 2007 to 2018. (13th November 2019) - Nardi, A; Migliara, G; Angelozzi, A; Caminada, S; Giffi, M; Isonne, C; Pirro, F A; Bertazzoni, G; Villari, P; Vito, C De
Abstract: Background: First generation immigrants are at high risk of psychiatric disorders (PD). Moreover, cultural and migration related factors can act as barriers in the access to care. The aim of this study was to analyze the emergency department (ED) visits and the subsequent admissions to Umberto I, a large teaching hospital in Rome, for PD from 2007 to 2018 and to highlight the differences between Italian citizens and foreigners. Methods: Adult patients were divided in 11 Nationality Groups (NGs). Basing on ICD9 codes, PD were classified in 5 categories: psychotic, mood, anxiety, personality and substance abuse disorders. Descriptive statistics were conducted for gender, age, educational level and triage. Poisson regression models, adjusted for sociodemographic variables, were used to estimate incidence rate ratios (IRRs) of different NGs, both for visits and hospital admissions, for the five psychiatric categories and for PD as a whole. Results: In the period of interest there were 11, 965 ED visits for PD, of which 19.2% made by foreigners. Compared to Italians, all NGs showed higher percentages of ED visits for PDs, except for Southern Asian (SA) and East-Southern east Asian (ESA); SA and ESA, together with Other Africa population, showed also higher proportion of psychosis. Regarding admissions, ESA had the highest percentage overall, while more than half of foreigner nationality groups had higher percentages of admissions for psychosis than Italians. Poisson regressions showed that only EU citizens have greater risk of ED visit (IRR 1.69, IC95% 1.46-1.96) and of hospital admission for PD (IRR 1.23, IC95% 1.02-1.49) than Italians, while Romanians, SA and ESA have lower risk. Conclusions: Different risk in ED visits for PDs among NGs can be due to heterogeneity in psychopathology, cultural factors, barriers, and migrant status. More studies are necessary to better understand the needs of foreigners and to enhance their mental health service use. Key messages: The risk of ED visit and hospital admission for psychiatric disorders differ among foreign populations. Different study design are needed to understand which cultural and migration related factors influence the risks, in order to provide more tailored mental health services for high risk populations.